'Berthing Bone': A poem. Issue 2 (1st December 2017) - Gray, Victoria
Berthing Bone (Gray, 2014) is a poem composed during the devising, filming and editing of an artists' moving image film. Conceived as a series of choreographed sculptures for the hands, the film performs a close-reading of the hand. Throughout the process of filming and post-production, a poetic text was written with the intent of performing an equally close, specifically kinaesthetic reading of the hand. During the exhibition of the film, the poem was performed live, alongside the screening. In the following artists' pages, the poem is transferred from the mouth to the page, and is accompanied by four stills from the Berthing Bone film. The reader is invited to read the poem aloud.